2021
DOI: 10.1155/2021/6657116
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Pile-Soil Synergistic Mechanism of Composite Foundation with Rigid Long and Short Piles

Abstract: The rigid long-short-pile composite foundation has been increasingly used as an effective and low-cost reinforcement method. The pile-soil interaction in this foundation type is more complicated than that in the equal-length pile composite foundation. In this study, several physical model tests were conducted to investigate the pile-soil synergistic mechanism of the rigid long-short-pile composite foundation. A comparative analysis was conducted of the static load test data of single-pile and long-short pile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…e determination of foundation bearing capacity is crucial in the design of foundation. erefore, the determination of foundation bearing capacity of frozen soil under freezing conditions through tests is also critical for application in practical projects [25][26][27][28][29][30][31][32][33][34]. rough the test and analysis in this chapter, it is concluded that when the temperature gradually decreases, due to the cementation of ice in the soil, the bearing capacity of the foundation will significantly increase.…”
Section: Test Methodmentioning
confidence: 95%
“…e determination of foundation bearing capacity is crucial in the design of foundation. erefore, the determination of foundation bearing capacity of frozen soil under freezing conditions through tests is also critical for application in practical projects [25][26][27][28][29][30][31][32][33][34]. rough the test and analysis in this chapter, it is concluded that when the temperature gradually decreases, due to the cementation of ice in the soil, the bearing capacity of the foundation will significantly increase.…”
Section: Test Methodmentioning
confidence: 95%
“…The model comprised structural (pile, raft and wall) and geotechnical (soil and cushion) parts that were modelled as elastic and elastic ideal plastic Mohr-Coulomb constitutive model, respectively. Even though Mohr-Coulomb model is not a state-of-the-art constitutive relation, it has widely been employed in FE analysis to describe the engineering characteristics of geotechnical materials while investigating the behaviour of composite piled raft foundations [6,10,[43][44][45] and performance of deep foundation pit excavations and/or their influence on the surrounding infrastructures. [26,46,47] Figure 1 depicts the typical meshed geometry employed in the model.…”
Section: Methodology Of Analysis 21 Finite Element Modellingmentioning
confidence: 99%
“…Often, in order to control the main target parameters and facilitate comparative experiments, model tests on composite foundations are necessary. Through model tests, we can not only understand the working mechanism of different types of composite foundations, including the working mechanism of long-and short-pile composite foundations [11,12], but also analyze the load transfer mechanism, deformation, and settlement laws of different types of composite foundations [13][14][15][16]. In some cases, the combined use of numerical simulations and experiments can provide a more comprehensive study of composite foundations.…”
Section: Introductionmentioning
confidence: 99%